Accuracy of Preoperative Endometrial Sampling for the Detection of Endometrial Pathology: a Retrospective Study - Keven P M Tali; Lilli M T Cole (Indonesian Journal of Obstetrics and Gynecology, 2017)
Objective: To investigate the accuracy of endometrial sampling in the diagnosis of endometrial pathology and the need of intraoperative frozen section. Methods: One hundred forty women who underwent endometrial sampling followed by hysterectomy between 2011 and 2014 were included in this study. Data were retrieved from patient files and pathology archives in Department of Obstetrics and Gynecology, Jose R. Reyes Memorial Medical Center, Manila, Philippines. Results: There were 25 patients with malignancy but endometrial sampling detected only 22 of them. The endometrial sampling sensitivity and specificity for detecting cancer were 88% and 100%, respectively with negative and positive predictive values of 97.5% and 100%, respectively. In 3 patients, the endometrial sampling failed to detect malignancy; 1 patient had a preoperative diagnosis of complex hyperplasia with atypia, 1 patient had complex hyperplasia without atypia and 1 patient had adenofibroma. A total of eighty patients had benign findings. There were fifty-three cases with finding of proliferative endometrium and twenty-seven were secretory. Twenty-three (55.0%) and 11 (39.0%) cases were confirmed by the hysterectomy specimen, respectively. The sensitivity of endometrial sampling in detecting benign samples was 76.0% and the specificity reached up to 83.0%. The histopathology result of the other fourteen cases were reported of having atrophy, twelve cases were reported of having endometrial hyperplasia, four with basal endometrium, four with endometrial polyp and one with adenomyosis. Conclusion: Outpatient endometrial biopsy has a high overall accuracy in diagnosing endometrial cancer when the specimen obtained is sufficient. A positive test result is more accurate for ruling in disease than a negative test result is for ruling it out. However, the diagnosis should be confirmed by frozen section in patients with complex hyperplasia and adenofibroma. [Indones J Obstet Gynecol 2017; 5-1: 23-29] Keywords: abnormal uterine bleeding, endometrial hyperplasia, endometrial sampling, frozen section, pipelle